Capital markets and the housing sector : perspectives on financial reform - Buckley, Robert M.; Tuccillo, John A.; Villani, Kevin E.; United States. Dept of Housing and Urban Development (Cambridge, Mass. : Ballinger Pub. Co., 1977)
This book is the contribution of scholars on the problems of housing finance in the United States. Papers are the result of study on housing finance. It also covers a wide variety subjects that will help in the financial reform of the housing sector.
Papers written chiefly in 1975 and early 1976 for a study conducted by the Office of Economic Affairs, Dept. of Housing and Urban Development.
Includes index.
Includes bibliographical references pp. 378-379
usc 14/07/2017
Loans
Keywords: Housing---Finance; Mortgage loans; United States